DETERMINAN PERILAKU KONSUMSI PANGAN MASYARAKAT DI DAERAH ISTIMEWA YOGYAKARTA (DIY) DAN NUSA TENGGARA TIMUR (NTT) - Tuti Ermawati; Jiwa Sarana (Jurnal Ekonomi dan Pembangunan, 2025)
The study analyzes the determinants of people’s food consumption behavior in two regions that have different food consumption patterns, namely DI Yogyakarta (DIY) and Nusa Tenggara Timur (NTT). In DIY, food consumption behavior has led to healthy food patterns so that analysis leads to determinants of healthy food consumption behavior. While in NTT, consumption behavior pattern is still oriented to staple food so that analysis leads to determinant of non staple food consumption of rice. The analytical method used in this study is path analysis with behavioral theory approach. Based on path analysis, the consumption of healthy family food in DIY is influenced by the intention of housewife in serving food. The intention of the housewife is influenced by the attitude formed by the knowledge and strong support from the closest person (husband). In addition, the intention is also strongly influenced by environmental control, especially family habits that prefer to consume their own processed foods. While in NTT, the intentions of housewives in serving non-rice staple food are influenced by attitude and environmental control. Attitudes are influenced by the skills and knowledges of housewives. While environmental control influenced family habits of consuming non-rice staple food and religious ceremonies. Hence, the government needs to do food consumption in accordance with the expectation, among others: First, increase promotion about the Desirable Dietary Pattern (DDP) in DIY and socialization of diversification of staple foods in NTT. Second, setting up training of varies healthy food processing for housewives considering that actually family members prefer processed food compared to instant food.